KOMUNIKASI TRADISIONAL PADA TRADISI MELAPU DI DESA ADAT BAYUNG GEDE KECAMATAN KINTAMANI KABUPATEN BANGLI - I Wayan Suarembawa; I Nengah Lestawi; I Made Sugata (Anubhava: Jurnal Ilmu Komunikasi HIndu, 2023)
Traditional communication media in the Melapu tradition (meetings) which are used very devoutly by the people of the Bayung Gede Traditional Village, Kintamani District, Bangli Regency in traditional activities, are associated with the utilization of the sophisticated development of modern communication media in the life of daily message information transaction transactions by the people of the Bayung Gede Traditional Village , is something very unique and interesting. With the formulation of the problem as follows: 1) Why is traditional communication in the Melapu tradition still used in the Bayung Gede Traditional Village? 2) What are the stages and processes of traditional communication in the Melapu tradition in Bayung Gede Traditional Village? 3) What are the implications of traditional communication on the Melapu tradition in Bayung Gede Traditional Village? This study uses a qualitative descriptive research type with a phenomenological approach, with data collection techniques through observation, mostly through in-depth interviews, documentation and literature studies, from primary data sources through key informants, main, supporting and secondary data sources. The results of this study are that traditional communication in the Melapu tradition is still very obedient to use in the Bayung Gede Traditional Village in traditional life, because the people of the Bayung Gede Traditional Village have resistance or resistance and rejection of changes that are not in accordance with tradition and carry out social actions in the form of traditional actions and value rationality while still holding fast to traditions that have been accepted and passed down by previous generations. The stages and processes of traditional communication in the Melapu tradition are carried out using a persuasive communication approach with communication components that can run effectively. The implications of traditional communication in the Melapu tradition are: survival of traditional beliefs, obedience and respect for traditions, the existence of Bayung Gede Traditional Village as a Bali Mula Village. Keywords: Traditional Communication, Melapu Tradition, Traditional Village